Urgensi Keberadaan Mujtahid Dalam Sengketa Waris (Perkara Waris Islam Dalam Putusan Nomor 596/PDT.G/2023/PA.SKA) - Cecareno Gilbrani Anwar; Mega Dewi Ambarwati (Tasfiyah : Journal of Islamic Law and Sharia Economics, 2025)
Inheritance disputes in Islamic law often require the role of mujtahids, especially judges, in interpreting and applying legal rules to achieve justice for the parties. The aim of this research is to analyze the role of the mujtahid in an inheritance dispute case involving the status of joint property, inherited assets, and the existence of the heir's debts. Based on Article 35 paragraph (1) of Law Number 1 of 1974 which has been amended by Law Number 16 of 2019, as well as Article 97 of the Compilation of Islamic Law, judges must ensure that the distribution of assets is carried out in accordance with the provisions of Islamic law. In this case, the judge as mujtahid considered that the property in dispute was joint property that had not been divided, so that the testator's widow was entitled to half the share before distributing the inheritance to the other heirs. Apart from that, in determining the existence of the heir's debt, the judge used the evidentiary principle in Article 163 HIR and Article 174 HIR, where the defendant's confession at trial was perfect evidence regarding the acknowledged debt. The research method uses normative legal research with a statutory approach and a case approach. The research results show that the role of the mujtahid in this case is not only limited to applying the law textually, but also considering aspects of substantive justice by referring to legal arguments, trial facts, and the principles of justice in Islam. Thus, the application of ijtihad by the judge in this case ensures that the distribution of inheritance is carried out legally, fairly and in accordance with applicable law. In decision number 596/Pdt.G/2023/PA.SKA in inheritance disputes, the decision is only resolved between the two parties to the dispute, so according to the author there is a need for the presence of a mujtahid in the inheritance dispute to provide clear legal certainty.